KORELASI ANTARA BUDAYA ORGANISASI DAN KOMITMEN ORGANISASI PADA KARYAWAN KONTRAK - Elvitha Fricilya Sou; Doddy Hendro Wibowo (Jurnal Inovasi Penelitian, 2022)
Organizational commitment is needed to support every company in achieving company goals. This study aims to determine the correlation organizational culture and organizational commitment to contract employees at PT. XX. This study uses a sample of 50 people who are contract employees of the machine maintenance division at PT.XX who have the criteria for the male sex, age 24-40 years, and length of work for 1-3 years using a saturated sampling technique. The measuring instruments used in this research are the Denison Organizational Culture Survey (DOCS) and the Self Report Scales. The results showed that there was a positive correlationetween organizational culture and organizational commitment to contract employees at PT. XX. The results of this study indicate that having a strong organizational culture will help every contract employee to have a high responsibility in achieving the desired company goals.